Development of styrene-butyl acrylate-isoprene emulsion copolymer coating for natural rubber gloves / Chareeya I gi - Chareeya , I gi (2022)
Coating natural rubber gloves with a layer of polymeric film is an essential process to improve donning properties of the gloves. In particular, polymeric coating with low coefficient of friction (CoF) is preferable for fast and easy donning. When coating an elastomeric article, there is an additional consideration where the coating layer can delaminate easily from the rubber substrate since the rubber article can be readily stretched. Hence, it is crucial to choose a right combination and composition of monomers to produce coating with a smooth surface and do not delaminate easily when stretched. In this research study, a newly developed styrene-butyl acrylate-isoprene (St-BA-Iso) emulsion copolymer was synthesized via seeded emulsion polymerization technique and the main objective of this study is to examine the effect of varying the composition of soft and hard monomers on the properties of emulsion and its coating performance in rubber gloves coating application. A series of St-BA-Iso emulsions of different monomers’ weight ratio were synthesized, and were subsequently formulated into polymeric coating solution to be coated on natural rubber film. The copolymers were characterized spectroscopically, as well as via microscopy, thermal and physical analyses. Carefully designed methodology and formulation has allowed the emulsions synthesis to achieve ≥ 90 % conversion, 41 ± 2 wt. % of total solid content, and desirable emulsions’ stability. In terms of coating performance on natural rubber film, copolymers comprised of higher loadings of soft monomers BA and Iso produced sticky films with a comparatively low glass transition temperature and higher CoF. Conversely, high loading of hard monomer St in the copolymer produced smooth coating surface with lower CoF but resulted in significant delamination from the rubber substrate when stretched due to high stiffness and poor coating adhesion. Of all synthesized copolymers, sample denoted as St-40 with 4 St: 3 BA: 3 Iso composition outperformed the rest as it was able to achieve a well-balanced donning properties, by demonstrating impressively smooth coating surface and at the same time retaining good coating adhesion on the rubber substrate. Hence, this makes St-40 an ideal copolymer emulsion for rubber glove coating applications.